2004
DOI: 10.1093/humupd/dmh019
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroidal regulation of uterine leiomyoma growth and apoptosis

Abstract: Uterine leiomyomas develop during the reproductive years and regress after menopause, indicating ovarian steroid-dependent growth potential. Although the clinical and biochemical observations have traditionally supported an important role for estrogen in the promotion of leiomyoma growth, there is also increasing evidence to suggest the involvement of progesterone in the pathogenesis of leiomyoma. In this review, much attention has been paid to characterizing the molecular mechanisms of sex steroidal regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
196
0
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(215 citation statements)
references
References 189 publications
3
196
0
15
Order By: Relevance
“…Sex hormones, such as oestrogen, are believed to play a major role in the growth of myomas [12,24,28,29]. The presence of oestrogen induces vesodilation leading to an increase in blood flow maintaining nutrient supply to the myoma cells [29].…”
Section: Effect Of Blood Flow On Growthmentioning
confidence: 99%
“…Sex hormones, such as oestrogen, are believed to play a major role in the growth of myomas [12,24,28,29]. The presence of oestrogen induces vesodilation leading to an increase in blood flow maintaining nutrient supply to the myoma cells [29].…”
Section: Effect Of Blood Flow On Growthmentioning
confidence: 99%
“…However, another study done on Pakistani patients depicted an up-regulation of Bcl-2 levels in nearly 50% of the leiomyomata. The mean level of Bcl-2 protein in the leiomyomatous tissue was greater than that of the adjacent normal myometrium but showed no statistically significant difference [p = 0.399] (24).…”
Section: Discussionmentioning
confidence: 99%
“…They presumed that progesterone could cause a reciprocal rise in Bcl-2 protein levels favouring an apoptosis inhibited environment within the tumour area (22,24).…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 has already been recognized as an inhibitor of the apoptotic process. Related to sex steroid hormones, Bcl-2 protein expression in leiomyoma cells has been extensively reported [25] . In this study, we noticed that there was no significant difference in Bcl-2 expression in the leiomyoma and myometrial cells, and this is supported by data previously reported by Wu et al [3] .…”
Section: Discussionmentioning
confidence: 99%